Clinical features of children with polycythemia vera, essential thrombocythemia, and primary myelofibrosis in Japan: A retrospective nationwide survey. Issue 1 (27th June 2020) - Ishida, Hisashi; Miyajima, Yuji; Hyakuna, Nobuyuki; Hamada, Satoru; Sarashina, Takeo; Matsumura, Risa; Umeda, Katsutsugu; Mitsui, Tetsuo; Fujita, Naoto; Tomizawa, Daisuke; Urayama, Kevin Y.; Ishida, Yasushi; et al.
Abstract: Background: Philadelphia‐negative (Ph‐negative) myeloproliferative neoplasms (MPNs), including polycythemia vera (PV), essential thrombocythemia (ET), and primary myelofibrosis (PMF), are exceptionally rare during childhood. Thus, clinical features of pediatric Ph‐negative MPNs remain largely unknown. This study was therefore performed to address this. Methods: We performed a retrospective study to collect clinical information of children diagnosed with Ph‐negative MPNs from 2000 to 2016 using questionnaires in qualified institutions in Japan. The results obtained from the questionnaire survey were then combined with those from the national registry data. Results: Among 50 children identified, five had PV, 44 had ET, and one had PMF. Median age at diagnosis was 14.0, 9.0, and 0 years, respectively. Male to female ratio was 4:1, 21:23, and 1:0, respectively. Detection rates of the JAK2 V617F variant were 0/5 in PV and 9/39 in ET. Frequencies of complications, such as thrombosis and subsequent leukemia, were lower than complication frequencies in adults. We identified two children who developed subsequent leukemia, which has not been reported previously, and one of them died. Conclusion: This is the first nationally representative survey of pediatric Ph‐negative MPNs. Given its rarity, an international collaboration with comprehensive genetic analyses might be needed to fully elucidate the clinical and genetic features.